Disain dan Analisis Generator Induksi Exitasi Sendiri pada Perubahan Nilai Kapasitor dan Kecepatan Penggerak Mula - , Setiyono (Jurnal Serambi Engineering, 2025)
This paper presents an analysis of the influence of changes in excitation capacitors and prime mover speed on the performance of power plants using three-phase induction generators. The objective is to determine the output parameters of voltage, current, active power, reactive power and torque of the induction generator when the generator is rotated by the prime mover at variable speed. The method used is to build a self-excited three-phase induction generator by installing three capacitors in parallel on the stator coil through modeling simulation using the Matlab Simulink tool. The simulation results show that changes in the capacitor and generator drive speed have an effect on the reactive power value produced by the generator.